Extraction of test cases procedures from textual use cases to reduce test effort: Test Factory Experience Report - dos Santos, Erick Barros; da Costa, Lucas Simão; Aragão, Bruno Sabóia; Santos, Ismayle de Sousa; Andrade, Rossana Maria de Castro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
The optimization of processes in the software development life cycle has become mandatory, since companies need to reduce the costs of their projects and shorten the time to market without affecting the quality of the product. With regards to software products, activities related to the testing process play a major role in their quality, since they assure that the product complies with the elicited requirements. However, companies usually do not perform testing activities on software projects due to financial and time constraints. These costs may be even higher in testing processes that rely on manual execution of activities, which is error-prone and can take too much time. To mitigate this situation, test automation allows the reduction of the effort required. This paper presents an experience report in a Test Factory about the use of a tool that partially automates the specification of test procedures based on use cases. The tool aims to read the textual use cases from the requirement management system, extract the test case procedures and required inputs to manual editing, and then send the test cases to the test management system. This solution is then applied to software from the telecommunications industry. This paper also presents how the tool was used and the lessons learned during the whole process.